Relation of early-stage renal insufficiency and cardiac structure and function in a large population of asymptomatic Asians: a cross-sectional cohort analysis - Wu, Pei-Chen; Sung, Kuo-Tzu; Lin, Jiun-Lu; Hung, Ta-Chuan; Lai, Yau-Huei; Su, Cheng-Huang; Yeh, Hung-I.; Wu, Chih-Jen; Hung, Chung-Lieh (Frontiers in Nephrology, 2023)
Background Few studies have addressed early-stage kidney disease and preclinical cardiac structural and functional abnormalities from a large-scale Asian population. Further, the extent to which measures of myocardial function and whether these associations may vary by testing various formulas of renal insufficiency remains largely unexplored. Objective To explore the associations among renal function, proteinuria, and left ventricular (LV) structural and diastolic functional alterations. Design A cross-sectional, retrospective cohort study. Setting Registered data from a cardiovascular health screening program at MacKay Memorial Hospital from June 2009 to December 2012. Participants Asymptomatic individuals. Measurements Renal function was evaluated in terms of estimated glomerular filtration rate (eGFR) by both MDRD and CKD-EPI formulas and severity of proteinuria, which were further related to cardiac structure, diastolic function (including LV e’ by tissue Doppler), and circulating N-terminal pro-brain natriuretic peptide (NT-proBNP) level. Results Among 4942 participants (65.8% men, mean age 49.4 ± 11.2 years), the mean CKD-EPI/MDRD eGFR was 90.6 ± 15.7 and 88.5 ± 16.9 ml/min/1.73m2, respectively. Lower eGFR, estimated either by the MDRD or CKD-EPI method, and higher proteinuria were significantly associated with lower LV e’ and higher NT-proBNP (all p<0.05) even after adjusting for clinical covariates. In general, lower eGFR estimated by CKD-EPI and MDRD displayed similar impacts on worsening e’ and NT-proBNP, rather than E/e’, in multivariate models. Finally, lower LV e’ or higher composite diastolic score, rather than E/e’, demonstrated remarkable interaction with eGFR level estimated by either CKD-EPI or MDRD on circulating NT-proBNP level (p interaction <0.05). Limitations Proteinuria was estimated using a urine dipstick rather than more accurately by the urine protein-to-creatinine ratio. Also, pertaining drug history and clinical hard outcomes were lacking. Conclusion Both clinical estimate of renal insufficiency by eGFR or proteinuria, even in a relatively early clinical stage, were tightly linked to impaired cardiac diastolic relaxation and circulating NT-proBNP level. Elevation of NT-proBNP with worsening renal function may be influenced by impaired myocardial relaxation.